Follicular Thyroid Cancer Metastasis to the Urinary Bladder: Report of a Case and Review of the Literature. (1st August 2012) - Grivas, N.; Housianitis, Z.; Doukas, M.; Stavropoulos, N. E.
Abstract : Thyroid cancer metastasis to the urinary bladder is a very rear condition. To the authors' knowledge there have been only 2 cases reported in the literature. Herein a case is reported of a metastatic bladder tumor in a 73-year-old woman with history of thyroid and breast cancer. Gross hematuria was the initial symptom of her metastatic disease. Pathology of the resected mass revealed a follicular thyroid cancer metastasis. This case illustrates that follicular carcinoma of the thyroid may have a variable presentation, including hematuria.